Is progress in energy-efficient comminution doomed?. (15th March 2015) - Napier-Munn, Tim
Highlights: Comminution is a large consumer of energy but is not seen as a priority issue. Internal and external pressures will change this situation. Much that has been learned about comminution has not yet been captured by industry. Comminution energy can be reduced substantially using new knowledge. This will require a global effort by the industry and research providers. Abstract: Comminution is known to be an inefficient user of energy. This makes it the largest energy consumer in many mine sites and therefore a large component of cost. One would therefore have thought that improving comminution energy efficiency would be receiving the undivided attention of the mining industry, but this is not the case. This paper considers why this is so and what the future might hold, by posing and attempting to answer three questions: Is this really an important issue for the mining industry? If so, can comminution energy be substantially reduced in a reasonable time frame? What are the drivers that will motivate change, and what should now be done? The conclusions of the paper are pessimistic in the sense that forces may be gathering that will demand that the issue be addressed across the industry in the relatively near future, but optimistic in the sense that there is a clear development path. There is much that can be done with what is already known, and considerable promise exists in new developments which can be realised through sustained and focused R&D, building on new knowledge acquired in the last 20 years. These are outlined in the paper. It is concluded that there is a case for a global initiative to significantly reduce comminution consumption over say the next 10 years through a partnership between all parts of industry and the research community, covering short, medium and long-term innovation.